THE CHANGES IN STREAM WATER TEMPERATURE AND WATER QUALITY PARAMETERS DURING RAINFALL EVENTS IN FORESTED WATERSHEDS: SCALING OF OBSERVATIONS - Luki Subehi; Takehiko Fukushima; Yuichi Onda; Shigeru Mizugald (Faculty of Geography, Universitas Gadjah Mada, 2010)
We studied the changes in stream water temperature (Tw) and waterquality (Wq) during rainfall events in forested watersheds. The parameters ofWq(88, DOC, N03–N, DTN, Na+, 8i and r) were observedinfour regionsof Japanfrom June 2004 to December 2005. The R values between Tw and those Wqparameters and between specific discharge (Qs) and Wq were positive, exceptforthe negativeones (Na+ and Si). Similarto the relationbetweenQs vs. Tw, hystereticloops in the relations between Qs vs. those Wqparameters were clockwise,exceptfor Na+ and Si as counter-clockwiseloops. This indicatesthat the'surfaceand subsurface flows contain higher concentrations of SS, DOC, IC, N03–N andDTN. To the contrary,the deeperpathwayscontainhigherconcentrationsof Na+and Si. These results suggest that the changes in Tw and Wq could be used tointerpret theflow paths.